Pengaruh Media Gambar Terhadap Minat Belajar Siswa pada Pembelajaran IPA Kelas IV SD Negeri 03 Sindang Danu - Wijaya, Andriansya; Imansyah, Farizal; Marleni, Marleni (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The formulation of the problem of this research is is there any influence of image media on students' interest in learning science in class IV SD Negeri 03 Sindang Danau? The purpose of this study was to determine whether or not there was an influence of image media on students' interest in learning science in class IV SD Negeri 03 Sindang Danau. The method used in this research is using True Experimental Design. The population in this study were all fourth grade students at SD Negeri 03 Sindang Danau, while the research sample was 18 students in class IV.A as the experimental class and 16 students in class IV.B as the control class. The data collection technique used a questionnaire. observation, and documentation, while the data analysis technique used the t test. Based on the results of the study, it was found that the average of the experimental group's questionnaire on learning interest in fourth grade students at SD Negeri 03 SD Negeri 03 Sindang Danau was 83.39, while the average control group questionnaire after being given picture media was 76.75. Thus, the averageinterest in learning with image media is higher than that without image media. Based on the results of hypothesis testing, it was found that the value of tcount ttable or 3.942 > 1.693889. Thus, it can be concluded that Ho is rejected and Ha is accepted or there is an influence of image media on students' learning interest in science learning for Class IV SD Negeri 03 Sindang Danau.